REDESIGN BRAND IDENTITY LOGO ZERO PARFUME - FIKRI ZARKI, Ir. Drs. Heldi, M.Si., Ph,.D. Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Zero Parfum is one of the business forms of refill (refill) in the city of Padang, this business has been pioneered by Ade Zalindro since 2016 located at Jl. Gajah 8 Air Tawar Barat Padang City. His business has progressed received a response from consumers. However, the underlying problem of the appearance of the Zero Parfum logo does not yet reflect the characteristics of identity as a brand, people's perceptions are similarities in the identity of the logo with other product brands.The purpose of the design of the Zero Parfum logo re-design is to present a logo that is simple, elegant, easy to remember, flexible, dynamic and communicative, reflecting the strong characteristics of being a visual identity and identity as the appearance of the informative and communicative Zero Perfume logo This logo designMethod uses Glass Box. Glass box method (glass box method) where thinking rationally objectively and systematically examines things logically and free from thoughts and considerations.The analytical approach uses the principle of 5W + 1H. The results of the design of the Zero Parfum logo redesign as the main media and supporting media: manual books, posters, menus, x-banners, paper bags, t-shirts, stickers, business cards, perfume bottles, stampsKey Words : Redesign, logo, Zero, Parfum.